Analysis of the track system in bumpy unstructured hard road environment by vibration test - Li, Mutong; Li, Junlue; He, Lin; He, Jie; Hu, Lian; Lyu, Chengxu (International Journal of Agricultural and Biological Engineering, 2022)
The complex terrain environment in the hilly land directly affects the operational reliability of agricultural robots. In order to study the impact of road irregularity on walking chassis vibration, the 3SYLZ-750 remote-controlled weeding machine which is applied to orchards was taken as the object of study, and the rear roller was selected as the object of observation to reveal the rules under which the vibration of the track chassis changes as there is a sudden change in road surface elevation. A column-type test-to-pass method based on unit excitation was proposed in this study. The excitation behavior and action process were analyzed by category. A critical acceleration prediction model was built and verified by virtual simulation and hard road surface excitation testing. The results showed that at the forward velocity of 0-2.5 km/h and exciter height of 20-100 mm, the vertical vibration acceleration of the target roller was significantly affected by Track Contact Point Centrifugal Acceleration (TCPCA). As TCPCA increased, the change rate of vertical vibration acceleration decreased, reaching a minimum of [−13.8, 28.8]; as TCPCA decreased, the vertical vibration acceleration tended to increase positively at a maximum variation range of [−13.3, 42.2]. The measured and simulated macroscopic change rules were consistent with the theoretical analysis, further verifying the correctness of variable extraction, and providing a research basis for the accurate modification and improvement of the model. The research conclusions can lay a theoretical foundation for analyzing the walking reliability of the track chassis, and provide a design basis and technical support for the development of a tracked agricultural robot chassis for the hilly land in the future. Keywords: track system, unstructured road, vibration test, simulation analysis, hilly land, agricultural robot DOI: 10.25165/j.ijabe.20221504.7249 Citation: Li M T, Li J L, He L, He J, Hu L, Lyu C X. Analysis of the track system in bumpy unstructured hard road environment by vibration test. Int J Agric & Biol Eng, 2022; 15(4): 163–171.